Efficacy and safety of daylight photodynamic therapy after tailored pretreatment with ablative fractional laser or microdermabrasion: a randomized, side‐by‐side, single‐blind trial in patients with actinic keratosis and large‐area field cancerization. (1st April 2019) - Wenande, E.; Phothong, W.; Bay, C.; Karmisholt, K.E.; Haedersdal, M.; Togsverd‐Bo, K.
Summary: Background: Physical pretreatments can potentiate the efficacy of daylight photodynamic therapy (dPDT), but clinical comparative studies remain limited. Objectives: Performed in large skin areas with actinic keratoses (AKs) and photodamage, this blinded, randomized clinical trial compared the efficacy and safety of dPDT after tailored skin pretreatment using ablative fractional laser (AFL) or microdermabrasion (MD). Methods: Two ≥ 50‐cm 2 side‐by‐side skin areas were randomized to receive a single treatment with AFL‐dPDT or MD‐dPDT. Pretreatment parameters were tailored according to AK grade and skin constitution to ensure standardized immediate end points. Subsequently, methyl aminolaevulinate was applied, followed by 2‐h daylight exposure. The primary outcome comprised blinded assessment of AK clearance at the 3‐month follow‐up. Results: In 18 patients with 832 AKs, AFL‐dPDT provided significantly higher AK clearance (81% vs. 60%, P < 0·001), led to fewer new AKs ( P < 0·001) and showed superior improvement in dyspigmentation ( P = 0·003) and skin texture ( P = 0·001) vs. MD‐dPDT. Peaking at days 3–6, AFL‐PDT induced more intensified local skin responses ( P = 0·004), including instances of Staphylococcus aureus infection ( n = 3). Patients nonetheless preferred AFL‐dPDT ( P = 0·077), due to lower pretreatment‐related pain ( P = 0·002) and superior cosmesis ( P = 0·035) and efficacy compared with MD‐dPDT. Conclusions: AFL‐dPDT is an effective treatment for patients with AK with extensive field cancerization, although AFL pretreatment is associated with intensified local skin reactions.